Proverbs, commitment, and the evasion of responsibility - Damien Villers (Anglophonia)
This article will tackle the different degrees and types of commitment at work in proverbial interaction. After an introduction to the notions of “commitment” and “proverb”, formal commitment will be briefly discussed through formulae that contain stance markers. More attention will then be paid to the sociolinguistic approach which describes proverbs as a way for the speaker to avoid commitment and tension. This theory will be studied through notions such as polyphony or proverb duelling, and will be questioned through examples in which proverbs create tension intentionally or unintentionally, thus failing to disengage the speaker’s responsibility. Finally, commitment in proverbs will be broached through their alleged prescriptive nature. The study of the utterances in the last part will be led with the language functions theory as a framework, and will aim at showing that proverbs can perform numerous functions other than the prescriptive or “conative” one, therefore highlighting various degrees and types of commitment for the speaker.